Tehmina Durrani’s Exposition of Great Britain’s Religious Hegemonic Designs in the Subcontinent in Blasphemy - Fasih ur Rehman (University of Chitral Journal of Linguistics and Literature, 2018)
This paper aims to analyze Tehmina Durrani’s Blasphemy in light of Gramsci’s theory of cultural hegemony. The paper dwells deep in the study of the religious hegemony of the colonial master in the subcontinent, particularly in the Muslim communities. Although the novel is set in after partition Pakistan, the issue discussed is very much related to the role of British imperialists in establishing religious hegemony. The paper takes a content-based analysis of the novel and unravels instances of religious hegemony. The plot of the novel illustrates how the British colonial masters, to subjugate the natives, fabricated the religious hegemonic ideas in the Muslim society of the subcontinent. Durrani has not only adroitly exposed the hegemonic designs of the British colonial masters, but she has also delineated the after-effects of such hegemonic ideas on the society in general, and on women in particular. This study also, from evidence present in the novel, tries to portray the history of shrines in the subcontinent and studies the behavior of the Pirs who rules these shrines and their attitudes towards women.